High-crystallinity hollow positive electrode precursor and preparation method and application thereof

The high crystallinity hollow positive electrode precursor was prepared by co-precipitation reaction method, which solved the structural stability and cyclic performance problems of nickel-rich layered positive electrode materials in lithium-ion batteries, and achieved a ternary positive electrode with high capacity and long-term cycle stability Materials significantly improve the cycle life of all solid state batteries.

CN119430316APending Publication Date: 2025-02-14JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411825888.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing nickel-rich layered cathode materials have problems such as Li+/Ni2+ cation mixed discharge, Li residue, poor thermal stability and material powdering in lithium-ion batteries, resulting in limited circulation and rate performance.

Method used

The high crystallinity hollow positive electrode precursor is prepared by co-precipitation reaction method. By regulating the feed rate and pH of the precipitant solution in the nucleation and growth stages, holes are formed inside the precursor particles to form high-definition with a specific morphology. Crystalline hollow positive electrode precursor.

Benefits of technology

The output characteristics and electrochemical activity of the ternary positive electrode material are improved, the structural stability and long-term cycle stability of the material are enhanced, and the cycle life of all solid state batteries is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430316A_ABST
    Figure CN119430316A_ABST
Patent Text Reader

Abstract

The invention provides a high-crystallinity hollow positive electrode precursor and a preparation method and application thereof. The method comprises the following steps: a ternary transition metal mixed salt solution, a precipitant solution and a complexing agent solution are introduced into a base solution in a parallel flow manner, a co-precipitation reaction is performed, feeding is stopped when particles subjected to the co-precipitation reaction grow to target particle sizes, and the high-crystallinity hollow positive electrode precursor is obtained, wherein the co-precipitation reaction comprises a nucleation stage and a growth stage, the feeding speed of a precipitant solution in the nucleation stage is smaller than the feeding speed of the precipitant solution in the growth stage, and the feeding speed of the precipitant solution in the co-precipitation reaction is smaller than 10 L / h. The ternary positive electrode material prepared from the high-crystallinity hollow positive electrode precursor provided by the invention has high capacity and also has good structural stability and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a high-crystallinity hollow positive electrode precursor and a preparation method and application thereof. Background Art

[0002] As a simple and efficient energy storage system, lithium-ion batteries are widely used in many fields such as electric vehicles, mobile power supplies, energy storage systems and electronic products because of their advantages such as high energy density, long life, safety and reliability. However, traditional liquid lithium-ion batteries have some safety issues during application, mainly including the flammability and explosiveness of organic electrolytes and internal short circuits caused by lithium dendrites penetrating the diaphragm. Based on this, solid electrolytes are used to replace flammable and explosive electrolytes to achieve the intrinsic safety of lithium-ion batteries. At the same time, positive and negative electrode materials with higher specific capacity can also be used to further improve the energy density of lithium-ion batteries.

[0003] Compared with commercial cathode materials such as lithium cobalt oxide, ternary transition metal oxide materials and lithium iron phosphate, nickel-rich layered materials (chemical formula LiNi 1-x-y Mn x Co y O2, where x+y≤0.4, referred to as NCM) is considered to be one of the most promising candidates for lithium-ion battery cathode materials, mainly due to its high capacity (220mAh / g) and high operating voltage (4.0V vs.Li + / Li). In fact, the nickel-rich layered materials synthesized so far have Li + / Ni 2+ Problems such as cation mixing, Li residue, poor thermal stability, and material pulverization due to large volume changes after multiple charge and discharge have limited the cycle performance and rate performance of the assembled lithium-ion battery. So far, researchers have tried a variety of technical means to improve the structural stability of nickel-rich layered materials, including element doping, surface coating, and forming a concentration gradient during the reaction process.

[0004] Although the element doping method can significantly improve the cycle stability of nickel-rich layered positive electrode materials, it will also bring about the problem of capacity reduction; and the surface coating method can isolate the electrolyte to a certain extent, but it will also increase the complexity of the preparation process.

[0005] Therefore, in this field, there is an urgent need to develop a positive electrode material with high specific capacity and stable structure and a preparation method thereof, so as to be suitable for all-solid-state batteries. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high-crystallinity hollow positive electrode precursor and a preparation method and application thereof, so as to ensure that the ternary positive electrode material prepared thereby has high capacity as well as good structural stability and cycle stability.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a high-crystallinity hollow cathode precursor, the method comprising the following steps:

[0009] The ternary transition metal mixed salt solution, the precipitant solution and the complexing agent solution are simultaneously introduced into the base solution to perform a coprecipitation reaction, and the feeding is stopped when the particles of the coprecipitation reaction grow to a target particle size, thereby obtaining the high-crystallinity hollow positive electrode precursor;

[0010] The coprecipitation reaction includes a nucleation stage and a growth stage, the feed rate of the precipitant solution in the nucleation stage is lower than the feed rate of the precipitant solution in the growth stage, and the feed rate of the precipitant solution in the coprecipitation reaction is lower than 10 L / h.

[0011] The present invention regulates the flow rate change of the precipitant solution during the nucleation stage and the growth stage, and controls the precipitant solution to have a lower feeding rate during the entire co-precipitation reaction, so that the pH value of the system drops rapidly, resulting in uneven growth of the inner core and outer shell of the precursor particles, and ultimately forming holes inside the precursor particles, forming a high-crystallinity hollow positive electrode precursor with a specific morphology.

[0012] The high-crystallinity hollow positive electrode precursor prepared by the present invention, on the one hand, has a hollow porous structure that is beneficial to broadening the lithium ion transmission channel of the prepared ternary positive electrode material, thereby improving the output characteristics of the ternary positive electrode material, and ultimately improving the electrochemical activity and capacity of the ternary positive electrode material; on the other hand, its high crystallinity is beneficial to improving the structural stability of the prepared ternary positive electrode material, thereby being able to improve the long-term cycle stability of the ternary positive electrode material.

[0013] Preferably, the ratio of the feed rate of the precipitant solution in the nucleation stage to the feed rate of the precipitant solution in the growth stage is 1:(1.0-1.5), preferably 1:(1.1-1.3), for example, it can be 1:1.0, 1:1.1, 1:1.15, 1:1.2, 1:1.25, 1:1.3, 1:1.35, 1:1.4, 1:1.45, 1:1.5, etc. The present invention regulates the feed rate ratio of the precipitant solution in the nucleation stage to the feed rate ratio of the precipitant solution in the growth stage, so that the growth rate of the inner core and the outer shell of the precursor particles are different, thereby generating voids. If the feed rate of the precipitant solution in the nucleation stage is high, too many crystal nuclei will be formed; if the feed rate of the precipitant solution in the growth stage is high, the growth rate of the precursor particles will be slow.

[0014] Preferably, the pH value in the nucleation stage is 10.6-11.8, and the concentration of ammonia is 1g / L-5g / L, preferably the pH value is 10.8-11.3, and the concentration of ammonia is 2g / L-5g / L. The pH value can be, for example, 10.6, 10.7, 10.8, 10.9, 11.0, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, etc.; the concentration of ammonia can be, for example, 1g / L, 1.5g / L, 2g / L, 2.5g / L, 3g / L, 3.5g / L, 4g / L, 4.5g / L, 5g / L, etc.

[0015] Preferably, the pH value in the growth stage is 8.0-11.0, and the concentration of ammonia is 1g / L-8g / L, preferably the pH value is 9.0-9.5, and the concentration of ammonia is 1g / L-3g / L. The pH value can be, for example, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, etc.; the concentration of ammonia can be, for example, 1g / L, 1.5g / L, 2g / L, 2.5g / L, 3g / L, 3.5g / L, 4g / L, 4.5g / L, 5g / L, 5.5g / L, 6g / L, 6.5g / L, 7g / L, 7.5g / L, 8g / L, etc.

[0016] Preferably, the pH value of the nucleation stage decreases uniformly at a rate of 0.2 / H to 0.6 / H and enters the growth stage, preferably decreases uniformly at a rate of 0.5 / H to 0.6 / H and enters the growth stage, for example, it can be 0.2 / H, 0.25 / H, 0.3 / H, 0.35 / H, 0.4 / H, 0.45 / H, 0.5 / H, 0.55 / H, 0.6 / H, etc.

[0017] The present invention adjusts the pH value, ammonia concentration and pH change rate during the nucleation and growth stages to ensure that the pores of the precursor meet the use requirements. If the pH value decreases too quickly, the pores in the core of the precursor will be larger, making it looser, and the structure of the prepared ternary cathode material will collapse easily.

[0018] Preferably, the coprecipitation reaction temperature is 30°C to 80°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, etc.

[0019] Preferably, the coprecipitation reaction is carried out under an inert atmosphere.

[0020] In the present invention, the inert atmosphere exemplarily includes at least one of nitrogen or argon.

[0021] Preferably, the pH value of the base solution is higher than the pH value of the coprecipitation reaction.

[0022] Preferably, the pH value of the base solution is 9.0-12.0, for example, it can be 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, etc.; the concentration of ammonia is 1g / L-5g / L, for example, it can be 1g / L, 1.5g / L, 2g / L, 2.5g / L, 3g / L, 3.5g / L, 4g / L, 4.5g / L, 5g / L, etc.

[0023] Preferably, the temperature of the base liquid is 30°C to 80°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, etc.

[0024] Preferably, the concentration of the ternary transition metal mixed salt solution is 50 g / L to 150 g / L, for example, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, etc.

[0025] Preferably, the feed rate of the ternary transition metal mixed salt solution is 6 L / h to 10 L / h, for example, 6 L / h, 7 L / h, 8 L / h, 9 L / h, 10 L / h, etc.

[0026] Preferably, the mass concentration of the precipitant solution is 20% to 50%, for example, it can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.

[0027] Preferably, the initial feed rate of the precipitant solution is 2 L / h to 3 L / h, for example, 2 L / h, 2.2 L / h, 2.5 L / h, 2.8 L / h, 3 L / h, etc.

[0028] Preferably, the mass concentration of the complexing agent solution is 10% to 20%, for example, 10%, 12%, 15%, 18%, 20%, etc.

[0029] Preferably, the initial feed rate of the complexing agent solution is 0.6 L / h to 1 L / h, for example, 0.6 L / h, 0.65 L / h, 0.7 L / h, 0.75 L / h, 0.8 L / h, 0.85 L / h, 0.9 L / h, 0.95 L / h, 1 L / h, etc.

[0030] Preferably, the target particle size is 2 μm to 5 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, etc.

[0031] In a second aspect, the present invention provides a high-crystallinity hollow-type positive electrode precursor, wherein the high-crystallinity hollow-type positive electrode precursor is prepared by the method for preparing a high-crystallinity hollow-type positive electrode precursor according to the first aspect.

[0032] Preferably, the half-peak width FWHM(101) of the X-ray diffraction test of the high-crystallinity hollow positive electrode precursor is less than 0.36°, and FWHM(001) is less than 0.45°, which further shows that the high-crystallinity hollow positive electrode precursor prepared by the present invention has a smaller half-peak width, indicating that the precursor particles have a higher degree of crystallinity, which is beneficial to improving the cycle performance of the prepared ternary positive electrode material.

[0033] Preferably, the peak intensity ratio of the high crystallinity hollow positive electrode precursor in the X-ray diffraction test is 0.65≤I(101) / I(001)≤0.85, which further shows that the high crystallinity hollow positive electrode precursor prepared by the present invention has a higher peak intensity ratio, indicating that the positive electrode precursor has a high degree of crystallinity, so that the ternary positive electrode material prepared therefrom has better stability during the charge and discharge process, thereby improving the cycle stability of the ternary positive electrode material and extending the service life of the assembled all-solid-state battery.

[0034] Preferably, the number of lamellae of the (101) crystal plane in the high crystallinity hollow cathode precursor is 100 to 120, and the number of lamellae is calculated as follows: Number of lamellae = D (101) / d,D (101) is the grain size corresponding to the (101) crystal plane, in nm; d is the lattice spacing, in nm. The present invention can shorten the transmission distance of lithium ions by increasing the number of lamellae of the (101) crystal plane. In addition, the (101) crystal plane is a vertical crystal plane for the lithium ion embedding / escape channel. Increasing the number of lamellae of the (101) crystal plane is conducive to improving the lithium ion conductivity, thereby improving the rate performance of the prepared ternary positive electrode material.

[0035] Preferably, the crystal deformation stacking fault rate f of the high crystallinity hollow cathode precursor is D ≤4%, the crystal deformation stacking fault rate is calculated as follows:

[0036] f D =0.1552FWHM (101) -0.03233FWHM (102) -0.4399 / D (001) , where FWHM (101) is the half maximum width of the (101) diffraction peak, FWHM (102) is the half-peak width of the (102) diffraction peak, unit: degree; D (001) is the grain size corresponding to the (001) crystal plane, in nm. The high-crystallinity hollow cathode precursor prepared by the present invention has a low crystal deformation stacking fault rate, so that the ternary cathode material prepared therefrom has good structural stability, thereby being able to improve the capacity of the assembled all-solid-state battery and comprehensively improve its long-term cycle stability.

[0037] In the present invention, the half-peak width of the X-ray diffraction test of the 101 crystal plane, 102 crystal plane and 001 crystal plane of the high crystallinity hollow positive electrode precursor can be obtained by testing using methods known in the art. As an example, a Bruker D8DISCOER model X-ray diffractometer can be used to scan the high crystallinity hollow positive electrode precursor at a slow speed (1° / min) of 2θ angle 10-80°, and perform spectrum fitting to obtain the relevant parameters of the diffraction peaks of the 001 crystal plane, 101 crystal plane, and 102 crystal plane.

[0038] In a third aspect, the present invention provides a ternary positive electrode material, wherein the ternary positive electrode material is prepared from the high crystallinity hollow positive electrode precursor according to the second aspect.

[0039] The ternary positive electrode material provided by the present invention is prepared by sintering the above-mentioned high-crystallinity hollow positive electrode precursor and a lithium source. The ternary positive electrode material inherits the precursor, and the structural characteristics and physicochemical indicators of the precursor material directly affect the comprehensive performance of the prepared ternary positive electrode material. Therefore, the positive electrode precursor with high crystallinity and hollow pore structure and the ternary positive electrode material prepared after sintering with a lithium source also have the characteristics of high crystallinity and hollow pore structure, thereby greatly enhancing the electrochemical performance and structural stability of the ternary positive electrode material, and improving its output power and long-term cycle stability.

[0040] In a fourth aspect, the present invention provides an all-solid-state battery, comprising a positive electrode, a negative electrode and a solid electrolyte, wherein the material of the positive electrode comprises the ternary positive electrode material according to the third aspect.

[0041] The ternary cathode material provided by the present invention is applied in an all-solid-state battery system, which greatly improves the cycle life of the all-solid-state battery.

[0042] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The present invention provides a method for preparing a high-crystallinity hollow positive electrode precursor. The prepared high-crystallinity hollow positive electrode precursor, on the one hand, has a hollow porous structure that is conducive to broadening the lithium ion transmission channel of the prepared ternary positive electrode material, thereby improving the output characteristics of the ternary positive electrode material, and ultimately improving the electrochemical activity and capacity of the ternary positive electrode material; on the other hand, its high crystallinity is conducive to improving the structural stability of the prepared ternary positive electrode material, thereby being able to improve the long-term cycle stability of the ternary positive electrode material.

[0045] The preparation method of the positive electrode precursor provided by the invention is simple and easy to implement and is suitable for large-scale production.

[0046] The all-solid-state battery assembled from the ternary cathode material provided by the present invention has good electrochemical performance, and its first discharge specific capacity at 0.1C is up to 235 mAh g -1 The capacity retention rate after 300 cycles at 0.1C is as high as 91.2%. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a SEM morphology image of the high-crystallinity hollow positive electrode precursor prepared in the present invention, with a scale of 1 μm.

[0048] Figure 2 This is a SEM morphology image of the high-crystallinity hollow positive electrode precursor prepared in the present invention, with a scale of 5 μm.

[0049] Figure 3 This is a SEM cross-sectional view of the high-crystallinity hollow positive electrode precursor prepared in the present invention, with a scale of 4 μm.

[0050] Figure 4 This is a SEM cross-sectional view of the high-crystallinity hollow positive electrode precursor prepared in the present invention, with a scale of 1 μm.

[0051] Figure 5 This is a SEM cross-sectional view of the high-crystallinity hollow positive electrode precursor prepared in the present invention, with a scale of 5 μm.

[0052] Figure 6 It is the X-ray diffraction pattern of the high-crystallinity hollow positive electrode precursor prepared in the present invention. DETAILED DESCRIPTION

[0053] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0054] Example 1

[0055] This embodiment provides a high-crystallinity hollow positive electrode precursor and a preparation method thereof, the preparation method comprising the following steps:

[0056] A 150 g / L nickel-cobalt-manganese mixed salt solution (wherein the molar ratio of nickel, cobalt and manganese is 96:3:1), a 25% sodium hydroxide solution and a 16% ammonia solution are simultaneously and concurrently fed into a reactor containing a base liquid having a temperature of 50°C, an ammonia concentration of 1 g / L and a pH value of 11.0 at feed rates of 8 L / h, 2.5 L / h and 0.8 L / h, respectively, and a coprecipitation reaction is carried out at a stirring rate of 300 r / min. The coprecipitation reaction includes a nucleation stage and a growth stage. The pH value in the nucleation stage is 11.0, the ammonia concentration is 2 g / L, the feed rate of the sodium hydroxide solution in the nucleation stage is 2.18 L / h, and the sodium hydroxide solution in the nucleation stage is 0.5 g / L. The ratio of the feed rate of the sodium hydroxide solution in the growth stage to the feed rate of the sodium hydroxide solution in the growth stage is 1:1.15, and the pH value in the nucleation stage decreases at a uniform rate of 0.55 / H to enter the growth stage. The pH value in the growth stage is 9.2, and the ammonia concentration is 2g / L. The reaction is then maintained at the above pH value. The reaction temperature is 40°C, and nitrogen is introduced throughout the process for protection. The particle size is continuously monitored. Before the particle size meets the requirement, a high-efficiency concentrator is used in the reaction process to collect all the particles and return them to the reactor for continuous reaction and growth. When the particles of the coprecipitation reaction grow to an average particle size of 3.5μm, the feed is stopped, and the reaction is continued until the material reaction is complete. After centrifugation and drying, the high-crystallinity hollow cathode precursor is obtained, and the chemical formula is Ni 0.96 Co 0.03 Mn 0.01 OH2.

[0057] from Figure 1-Figure 2 It can be seen that the shell of the high-crystallinity hollow cathode precursor in this embodiment has a dense structure; Figure 3-Figure 5 It can be seen that the interior of the high-crystallinity hollow positive electrode precursor in this embodiment presents a hollow structure.

[0058] This embodiment also provides a ternary positive electrode material and a preparation method thereof, which comprises the following steps:

[0059] The high crystallinity hollow positive electrode precursor is mixed with lithium carbonate, wherein the molar ratio of lithium element in lithium carbonate to all metal elements in the high crystallinity hollow positive electrode precursor is 1.05:1, and calcined at 450°C for 5h in an air atmosphere; the obtained sintered product is pressed into a compact and dense sheet, and then sintered at 900°C for 11h, and immediately quenched with liquid nitrogen after sintering to obtain a ternary positive electrode material with a chemical formula of LiNi 0.96 Co 0.03 Mn 0.01 O2.

[0060] Example 2

[0061] This embodiment provides a high-crystallinity hollow positive electrode precursor and a preparation method thereof, the preparation method comprising the following steps:

[0062] A nickel-cobalt-manganese mixed salt solution with a concentration of 150 g / L (wherein the molar ratio of nickel element, cobalt element and manganese element is 96:3:1), a sodium hydroxide solution with a mass concentration of 25%, and an ammonia solution with a mass concentration of 16% are simultaneously and concurrently introduced into a reactor containing a base liquid with a temperature of 50°C, an ammonia concentration of 2 g / L, and a pH value of 10.8 at feed rates of 8 L / h, 2.5 L / h, and 0.8 L / h, respectively, and a coprecipitation reaction is carried out at a stirring rate of 300 r / min. The coprecipitation reaction includes a nucleation stage and a growth stage. The pH value in the nucleation stage is 10.8, the ammonia concentration is 3 g / L, the feed rate of the sodium hydroxide solution in the nucleation stage is 2.28 L / h, and the sodium hydroxide solution in the nucleation stage is 0.5 g / L. The ratio of the feeding rate of the liquid to the feeding rate of the sodium hydroxide solution in the growth stage is 1:1.1, and the pH value in the nucleation stage is uniformly reduced at a rate of 0.5 / H to enter the growth stage. The pH value in the growth stage is 9.0, the concentration of ammonia is 1g / L, and then the reaction is maintained at the above pH value. The reaction temperature is 40°C, and nitrogen is introduced throughout the process for protection. The particle size is continuously monitored. Before the particle size meets the requirement, a high-efficiency concentrator is used in the reaction process to collect all the particles and return them to the reactor for continuous reaction and growth. When the particles of the coprecipitation reaction grow to an average particle size of 3.5μm, the feeding is stopped, and the reaction is continued until the material reaction is complete. After centrifugation and drying, the high-crystallinity hollow positive electrode precursor is obtained, and the chemical formula is Ni 0.96 Co 0.03 Mn 0.01 OH2.

[0063] The preparation method of the ternary positive electrode material in this embodiment is the same as that in Embodiment 1.

[0064] Example 3

[0065] This embodiment provides a high-crystallinity hollow positive electrode precursor and a preparation method thereof, the preparation method comprising the following steps:

[0066] A nickel-cobalt-manganese mixed salt solution with a concentration of 150 g / L (wherein the molar ratio of nickel element, cobalt element and manganese element is 96:3:1), a sodium hydroxide solution with a mass concentration of 25%, and an ammonia solution with a mass concentration of 16% are simultaneously and concurrently introduced into a reactor containing a base liquid with a temperature of 50°C, an ammonia concentration of 4 g / L, and a pH value of 11.5 at feed rates of 8 L / h, 2.5 L / h, and 0.8 L / h, respectively, and a coprecipitation reaction is carried out at a stirring rate of 300 r / min. The coprecipitation reaction includes a nucleation stage and a growth stage. The pH value in the nucleation stage is 11.3, the ammonia concentration is 2.5 g / L, the feed rate of the sodium hydroxide solution in the nucleation stage is 2.08 L / h, and the sodium hydroxide solution in the nucleation stage is 0.5 g / L. The ratio of the feeding rate of the solution to the feeding rate of the sodium hydroxide solution in the growth stage is 1:1.2, and the pH value in the nucleation stage decreases at a uniform rate of 0.6 / H to enter the growth stage. The pH value in the growth stage is 9.5, and the concentration of ammonia is 3g / L. Then the reaction is maintained at the above pH value, the reaction temperature is 40°C, and nitrogen is introduced throughout the process for protection. The particle size is continuously monitored. Before the particle size meets the requirement, a high-efficiency concentrator is used in the reaction process to collect all the particles and return them to the reactor for continuous reaction and growth. When the particles of the coprecipitation reaction grow to an average particle size of 3.5μm, the feeding is stopped, and the reaction is continued until the material reaction is complete. After centrifugation and drying, the high-crystallinity hollow positive electrode precursor is obtained, and the chemical formula is Ni 0.96 Co 0.03 Mn 0.01 OH2.

[0067] The preparation method of the ternary positive electrode material in this embodiment is the same as that in Embodiment 1.

[0068] Example 4

[0069] This embodiment provides a high-crystallinity hollow positive electrode precursor and a preparation method thereof, the preparation method comprising the following steps:

[0070] A 50 g / L nickel-cobalt-manganese mixed salt solution (wherein the molar ratio of nickel, cobalt and manganese is 96:3:1), a 20% sodium hydroxide solution and a 10% ammonia solution are simultaneously and concurrently fed into a reactor containing a base liquid having a temperature of 50°C, an ammonia concentration of 2 g / L and a pH value of 10.6 at feed rates of 6 L / h, 3 L / h and 0.6 L / h, respectively, and a coprecipitation reaction is carried out at a stirring rate of 300 r / min. The coprecipitation reaction includes a nucleation stage and a growth stage. The pH value in the nucleation stage is 10.6, the ammonia concentration is 1 g / L, the feed rate of the sodium hydroxide solution in the nucleation stage is 2.5 L / h, and the sodium hydroxide solution in the nucleation stage is 0.6. The ratio of the feed rate of the sodium hydroxide solution in the growth stage to the feed rate of the sodium hydroxide solution in the growth stage is 1:1.0, and the pH value in the nucleation stage decreases at a uniform rate of 0.2 / H to enter the growth stage. The pH value in the growth stage is 8.0, and the ammonia concentration is 1g / L. The reaction is then maintained at the above pH value. The reaction temperature is 40°C, and nitrogen is introduced throughout the process for protection. The particle size is continuously monitored. Before the particle size meets the requirement, a high-efficiency concentrator is used in the reaction process to collect all the particles and return them to the reactor for continuous reaction and growth. When the particles of the coprecipitation reaction grow to an average particle size of 2μm, the feed is stopped, and the reaction is continued until the material reaction is complete. After centrifugation and drying, the high-crystallinity hollow cathode precursor is obtained, and the chemical formula is Ni 0.96 Co 0.03 Mn 0.01 OH2.

[0071] The preparation method of the ternary positive electrode material in this embodiment is the same as that in Embodiment 1.

[0072] Example 5

[0073] This embodiment provides a high-crystallinity hollow positive electrode precursor and a preparation method thereof, the preparation method comprising the following steps:

[0074] A 150 g / L nickel-cobalt-manganese mixed salt solution (wherein the molar ratio of nickel, cobalt and manganese is 96:3:1), a 35% sodium hydroxide solution and a 20% ammonia solution are simultaneously and concurrently fed into a reactor containing a base liquid having a temperature of 70°C, an ammonia concentration of 5 g / L and a pH value of 12.0 at feed rates of 10 L / h, 3 L / h and 1 L / h, respectively, and a coprecipitation reaction is carried out at a stirring rate of 300 r / min. The coprecipitation reaction includes a nucleation stage and a growth stage. The pH value in the nucleation stage is 11.8, the ammonia concentration is 5 g / L, the feed rate of the sodium hydroxide solution in the nucleation stage is 1.67 L / h, and the sodium hydroxide solution in the nucleation stage is 0.5 g / L. The ratio of the feed rate of the sodium hydroxide solution in the growth stage to the feed rate of the sodium hydroxide solution in the growth stage is 1:1.5, and the pH value in the nucleation stage decreases at a uniform rate of 0.6 / H to enter the growth stage. The pH value in the growth stage is 11.0, and the ammonia concentration is 8g / L. The reaction is then maintained at the above pH value. The reaction temperature is 60°C, and nitrogen is introduced throughout the process for protection. The particle size is continuously monitored. Before the particle size meets the requirement, a high-efficiency concentrator is used in the reaction process to collect all the particles and return them to the reactor for continuous reaction and growth. When the particles of the coprecipitation reaction grow to an average particle size of 5μm, the feed is stopped, and the reaction is continued until the material reaction is complete. After centrifugation and drying, the high-crystallinity hollow cathode precursor is obtained, and the chemical formula is Ni 0.96 Co 0.03 Mn 0.01 OH2.

[0075] The preparation method of the ternary positive electrode material in this embodiment is the same as that in Embodiment 1.

[0076] Example 6

[0077] The difference between this embodiment and embodiment 1 is that the ratio of the feeding rate of the sodium hydroxide solution in the nucleation stage to the feeding rate of the sodium hydroxide solution in the growth stage is 1:2, so that the pH value in the nucleation stage is 11.2 and the pH value in the growth stage is 11.8. The rest is the same as embodiment 1.

[0078] Example 7

[0079] The difference between this embodiment and embodiment 1 is that the pH value in the nucleation stage decreases at a uniform rate of 0.05 / H to enter the growth stage, and the rest is the same as embodiment 1.

[0080] Example 8

[0081] The difference between this embodiment and embodiment 1 is that the pH value in the nucleation stage decreases uniformly at a rate of 1.2 / H to enter the growth stage, and the rest is the same as embodiment 1.

[0082] Example 9

[0083] The difference between this embodiment and embodiment 1 is that the pH value of the base liquid is 13.0, and the rest is the same as embodiment 1.

[0084] Comparative Example 1

[0085] The difference between this comparative example and Example 1 is that the ratio of the feeding rate of the sodium hydroxide solution in the nucleation stage to the feeding rate of the sodium hydroxide solution in the growth stage is 1:1, so that the pH value in the nucleation stage is 11.2, and the pH value in the growth stage is 11.2, and the rest is the same as Example 1.

[0086] Comparative Example 2

[0087] The difference between this comparative example and Example 1 is that the ratio of the feeding rate of the sodium hydroxide solution in the nucleation stage to the feeding rate of the sodium hydroxide solution in the growth stage is 2:1, so that the pH value in the nucleation stage is 11.6. Since crystal nuclei are continuously formed, further growth is impossible. The rest is the same as Example 1.

[0088] Comparative Example 3

[0089] The difference between this comparative example and Example 1 is that the ratio of the feeding rate of the sodium hydroxide solution in the nucleation stage to the feeding rate of the sodium hydroxide solution in the growth stage is 1:1.15, and the feeding rate of the sodium hydroxide solution in the nucleation stage is 20L / h, and the others are the same as Example 1.

[0090] Test conditions

[0091] The high crystallinity hollow positive electrode precursor provided in Example 1 was subjected to a structural performance test. The test conditions were as follows: a Bruker D8DISCOER X-ray diffractometer was used to scan the high crystallinity hollow positive electrode precursor at a slow speed (1° / min) at a 2θ angle of 10-80° to obtain the XRD raw data of the sample, as shown in Table 1. The X-ray powder diffraction comprehensive analysis software PDXL (manufactured by Rigaku Corporation) was then used to refine and calculate the data to obtain the grain size corresponding to each crystal plane, the diffraction peak intensity corresponding to each diffraction peak, the half-peak width and other data. Finally, the peak intensity ratio of the two specified diffraction peaks, the grain size of the crystal plane corresponding to the diffraction peak, the number of crystal plane layers and other related parameters were calculated.

[0092] In summary, if Figure 6As shown, the half-peak width FWHM (101) of the X-ray diffraction test of the high crystallinity hollow cathode precursor in Example 1 is 0.35°, FWHM (001) is 0.42°, and FWHM (102) is 0.43°; I (101) / I (001) is 0.83; the grain size corresponding to the (101) crystal plane is 253nm, d is 2.35nm, and the number of layers of the (101) crystal plane is calculated to be 108; the grain size corresponding to the (001) crystal plane is 202nm, and the crystal deformation stacking fault rate f is calculated to be D It is 3.85%.

[0093] Table 1

[0094]

[0095]

[0096] The ternary cathode materials provided in Examples 1 to 9 and Comparative Examples 1 to 3 were used to prepare all-solid-state batteries and then the electrochemical performance was tested. The test conditions were:

[0097] The ternary positive electrode materials provided in Examples 1 to 9 and Comparative Examples 1 to 3, Li3InCl6 (commercially available) and Super P (commercially available) were mixed in a mass ratio of 96:3:1 to obtain a mixed positive electrode powder.

[0098] Under an argon atmosphere, 8 mg of the above-mentioned mixed positive electrode powder was evenly distributed at the bottom of an all-solid-state mold made of PTFE with an inner diameter of 10 mm, and then 80 mg of Li6PS5Cl solid electrolyte powder (commercially available) was added on the mixed positive electrode powder, and then 30 mg of negative electrode material (the negative electrode material is a LiIn alloy film with a molar ratio of In to Li of 3:1, commercially available) was evenly distributed on the Li6PS5Cl solid electrolyte powder. Finally, a pressure of 3T was applied to the upper and lower ends of the all-solid-state mold and the pressure was maintained to fix it, thereby assembling an all-solid-state battery.

[0099] The Blue Electric test system was used to test the capacity retention rate of the all-solid-state battery at a charge cut-off voltage of 4.4V and after 300 cycles at 0.1C.

[0100] The test results are shown in Table 2:

[0101] Table 2

[0102]

[0103]

[0104] It can be seen from Table 2 that the ternary positive electrode material prepared from the high-crystallinity hollow positive electrode precursor provided by the present invention inherits the structural characteristics of the precursor, that is, it has high crystallinity and a hollow structure, so that the ternary positive electrode material has good structural stability, high specific capacity and long-term cycle stability, thereby significantly improving the cycle life of the assembled all-solid-state battery.

[0105] By comparing Example 1 and Example 6 with Comparative Examples 1 to Comparative Examples 3, it can be seen that the present invention adjusts the ratio of the feed rate of the sodium hydroxide solution in the nucleation stage to the feed rate of the sodium hydroxide solution in the growth stage and the feed rate of the sodium hydroxide solution during the entire co-precipitation reaction process, so that the growth rates of the inner core and the outer shell of the precursor particles are different, thereby generating voids.

[0106] By comparing Example 1, Example 7 and Example 8, it can be seen that the present invention adjusts the rate of change of the pH value so that the core of the precursor has suitable pores to avoid easy collapse of the structure.

[0107] By comparing Example 1 and Example 9, it can be seen that if the pH value of the base solution is too high, the prepared ternary positive electrode material will also have poor electrochemical performance.

[0108] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a high-crystallinity hollow cathode precursor, characterized in that: The method comprises the following steps: The ternary transition metal mixed salt solution, the precipitant solution and the complexing agent solution are simultaneously introduced into the base solution to perform a coprecipitation reaction, and the feeding is stopped when the particles of the coprecipitation reaction grow to a target particle size, thereby obtaining the high-crystallinity hollow positive electrode precursor; The coprecipitation reaction includes a nucleation stage and a growth stage, the feed rate of the precipitant solution in the nucleation stage is lower than the feed rate of the precipitant solution in the growth stage, and the feed rate of the precipitant solution in the coprecipitation reaction is lower than 10 L / h.

2. The method according to claim 1, characterized in that The ratio of the feed rate of the precipitant solution in the nucleation stage to the feed rate of the precipitant solution in the growth stage is 1:(1.0-1.5), preferably 1:(1.1-1.3); Preferably, the pH value in the nucleation stage is 10.6-11.8, and the concentration of ammonia is 1 g / L-5 g / L, preferably the pH value is 10.8-11.3, and the concentration of ammonia is 2 g / L-5 g / L; Preferably, the pH value in the growth stage is 8.0-11.0, and the concentration of ammonia is 1 g / L-8 g / L, and preferably the pH value is 9.0-9.5, and the concentration of ammonia is 1 g / L-3 g / L.

3. The method according to claim 1 or 2, characterized in that: The pH value of the nucleation stage decreases uniformly at a rate of 0.2 / H to 0.6 / H and then enters the growth stage, preferably, the pH value of the nucleation stage decreases uniformly at a rate of 0.5 / H to 0.6 / H and then enters the growth stage.

4. The method according to any one of claims 1 to 3, characterized in that The temperature of the coprecipitation reaction is 30°C to 80°C; Preferably, the coprecipitation reaction is carried out under an inert atmosphere.

5. The method according to any one of claims 1 to 4, characterized in that The pH value of the base solution is higher than the pH value of the coprecipitation reaction; Preferably, the pH value of the base solution is 9.0 to 12.0, and the concentration of ammonia is 1 g / L to 5 g / L; Preferably, the temperature of the base liquid is 30°C to 80°C.

6. The method according to any one of claims 1 to 5, characterized in that The concentration of the ternary transition metal mixed salt solution is 50 g / L to 150 g / L; Preferably, the feed rate of the ternary transition metal mixed salt solution is 6L / h to 10L / h; Preferably, the mass concentration of the precipitant solution is 20% to 50%; Preferably, the initial feed rate of the precipitant solution is 2L / h to 3L / h; Preferably, the mass concentration of the complexing agent solution is 10% to 20%; Preferably, the initial feed rate of the complexing agent solution is 0.6L / h to 1L / h; Preferably, the target particle size is 2 μm to 5 μm.

7. A high crystallinity hollow cathode precursor, characterized in that: The high-crystallinity hollow-type positive electrode precursor is prepared by the method for preparing a high-crystallinity hollow-type positive electrode precursor according to any one of claims 1-6.

8. The high crystallinity hollow cathode precursor according to claim 7, characterized in that: The half-peak width FWHM (101) of the X-ray diffraction test of the high-crystallinity hollow positive electrode precursor is less than 0.36°, and the FWHM (001) is less than 0.45°; Preferably, the peak intensity ratio of the high crystallinity hollow cathode precursor measured by X-ray diffraction is 0.65≤I(101) / I(001)≤0.85; Preferably, the number of lamellae of the (101) crystal plane in the high crystallinity hollow cathode precursor is 100 to 120, and the number of lamellae is calculated as follows: Number of lamellae = D (101) / d,D (101) is the grain size corresponding to the (101) crystal plane, in nm; d is the lattice spacing, in nm; Preferably, the crystal deformation stacking fault rate f of the high crystallinity hollow cathode precursor is D ≤4%, the crystal deformation stacking fault rate is calculated as follows: D =0.1552FWHM (101) -0.03233FWHM (102) -0.4399 / D (001) , where FWHM (101) is the half maximum width of the (101) diffraction peak, FWHM (102) is the half-peak width of the (102) diffraction peak, unit: degree; D (001) is the grain size corresponding to the (001) crystal plane, in nm.

9. A ternary positive electrode material, characterized in that: The ternary positive electrode material is prepared from the high-crystallinity hollow positive electrode precursor according to claim 7 or 8.

10. An all-solid-state battery, characterized in that: The all-solid-state battery comprises a positive electrode, a negative electrode and a solid electrolyte, and the material of the positive electrode comprises the ternary positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Hollow porous ternary positive electrode material, preparation method thereof and lithium ion battery

    CN113830844A

  • Hollow ternary positive electrode material and preparation method thereof

    CN115000383A

  • Radial positive electrode precursor and preparation method and application thereof

    CN118978192A

  • Lithium-nickel-cobalt-aluminum composite oxide and lithium ion secondary battery

    JP2020176050A